Workload doesn’t mean exhaustion: Antecedents of teacher burnout - Dung, Vu; Trang, Vu Thu; Lan, Nguyen Thi Mai (Journal of Education and e-Learning Research, 2024)
Workload has consistently been found to be a predictor of burnout in teachers. However, while academia considers workload a psychological concept, the public tends to simplify workload as the number of tasks assigned. This study seeks to provide further evidence of the psychological nature of workload by examining if workload understood in terms of quantity of work had any effect on teacher burnout and whether this relationship was moderated by psychological processes such as self-efficacy and mediated by stress. 117 primary and high school teachers holding at least two roles at school participated in the study. Teacher burnout was measured using MBI-ES, self-efficacy was measured by OSTES and stress and workload were measured by single-item questions. Results showed that workload (i.e., the number of roles assigned) did not have a main effect on burnout. Perceived stress and self-efficacy had direct effects on teacher burnout: stress increased burnout while self-efficacy reduced burnout. Self-efficacy had a significant moderation effect on workload-burnout interaction. Workload increased burnout only in teachers with low self-efficacy while stress did not moderate the workload-burnout relationship. These findings support the psychological nature of the relationship between workload and burnout among teachers. They also point out the importance of enhancing teacher stress management and self-efficacy in protecting them from burnout.